The Innovative Method for Vaccine Preparation Against Multidrug Resistant and Virulence Acinetobacter baumannii Iraqi Isolates - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
The expanding of the medically important diseases created by multidrug-resistant Acinetobacter baumannii warrants the evolve a new methodology for prevention includes vaccination and treatment. Totally of forty-five clinical isolates identified as A.baumannii were obtained from hospitalized patients from three hospital in Baghdad City during the period from February 2016 to August 2016. Followed by diagnosing using different methods. Every strain was tested for susceptibility testing also some important virulence factorswere detected. Two isolates were chosen for the immunization and vaccine model, the first one remittent for most antibiotics except one are too virulence (strong) and the second is less virulent and resistance (weak).Enzyme-linked immunosorbent assaywas used for assessments of Toll like receptor 4,and Toll like receptor 2 concentrations in mouse serum at 14, 21 and 28 days of immunization. Results proved that the strong isolate showed resistance to all antibiotics except one and positive to all virulence factors except one, while the weak isolate resistance to Ceftriaxone, Cefotaxime, positive to tow virulence factors. Mice were intramuscular inoculated with strong and weak isolate. There are high significant differences when using strong A.baumannii strong in the level of TLR4 and there was not an important variation among the use of strong and weak isolation in the level of TLR2.Finaly,the yield refers to the TLR4 plays a key role in innate sensing with multidrug resistance isolate immunization, whereas TLR 2 shows it gives the same level of stimulation during immunization with both strains but lesser concentration than TLR4, so the inactivated with MDR isolate has a potential for development as a candidate vaccine for strong protection against MDR isolate infections.